Long-term fire and vegetation change in northwestern Amazonia - Heijink, Britte; Mattijs, Q.A.; Philip, A.L.; Valencia, R.; Piperno, D.; McMichael, C.N.H. (Dryad, 2022)
Amazonian forest plots are used to quantify biodiversity and carbon
sequestration, and provide the foundation for much of what is known about
tropical ecology. Many plots are assumed to be undisturbed, but recent
work suggests that past fire, forest openings, and cultivation created
vegetation changes that have persisted for decades to centuries
(ecological legacies). The Yasuní Forest Dynamics plot is one of the most
biodiverse places on earth, yet its human history remains unknown. Here,
we use charcoal and phytolith analysis to investigate the fire and
vegetation history of the Yasuní forest plot, and compare results with
nearby forest plots in Colombia (Amacayacu) and Peru (Medio
Putumayo-Algodón (MPA)) to explore the spatial variability of past
disturbances and ecological legacies in northwestern Amazonia. Three 14C
dated charcoal fragments provided evidence for a modern (1956 CE) and a
past fire event ca. 750 years ago at Yasuní, compared with fire ages of
1000-1600 years ago documented at Amacayacu and MPA. Small-scale
disturbances and localized canopy-openings also occurred in the Yasuní
plot. Phytolith assemblages from Yasuní and Amacayacu showed more
variability in past vegetation change than MPA. Low-intensity,
non-continuous disturbances occurred at all three plots in the past, and
our results highlight the variability of past human activities both in
space and time in northwestern Amazonia. Our data also suggest that
post-Columbian human disturbances from the Rubber Boom (AD 1850-1920) and
subsequent oil exploration have likely left stronger ecological legacies
than those left by pre-Columbian peoples in our studied regions.
Samples were collected in Yasuní Forest Dynamics Plot and analyzed at the
University of Amsterdam (see Heijink et al., (2022) for more details).
Phytoliths were identified using published reference photographs (Huisman
et al., 2018, Morcote-Ríos et al., 2016, Piperno, 2006, Piperno and
McMichael, 2020, Witteveen et al., 2022) and the phytolith reference
collection of the University of Amsterdam.
Keywords: Charcoal; ecological legacies; forest plots; hyperdominants; past; phytoliths; tropical rainforest; FOS: Biological sciences